Buying knowledge : effective acquisition of external knowledge - Sammons, Peter (Routledge, 2018)
"Technology acquisition, consultancy know-how, research data and services, marketing information, intellectual property. the list of sources and types of knowledge that organizations need to acquire, share and manage is growing exponentially. The acquisition and management of knowledge as an end in itself is relatively new, but has grown in importance on most managers? agendas over the past fifteen years and is something that many managers are still fundamentally ill-equipped to control effectively. Yet it is their ability to plan, source, evaluate, acquire and manage knowledge on which the success of their organizations increasingly depends Peter Sammons provides managers with a readable, highly practical guide to buying and managing knowledge. The author looks at the knowledge economy, to set the scene on the manager's growing responsibility to buy-in knowledge for their organization. He explores intellectual property rights: how they are created, transferred and protected. He sets out some alternative strategies to buying knowledge. There's advice on how to work with universities, contract research organizations and consultancy firms. And the most neglected area of all - knowledge transfer from supplier to buyer - is given exhaustive treatment. In a discipline (knowledge work) that is fraught with jargon, technology and arcane practice, Buying Knowledge enables every manager to acquire the knowledge their organization needs; in a form and at a cost that is most appropriate for them without exposing their organization to litigation or intellectual property disputes."--Provided by publisher